Bhimamycin J, a Rare Benzo[f]isoindole‐dione Alkaloid from the Marine‐Derived Actinomycete Streptomyces sp. MS180069. Issue 11 (27th October 2021) - Song, Fuhang; Yang, Na; Khalil, Zeinab G.; Salim, Angela A.; Han, Jiahui; Bernhardt, Paul V.; Lin, Rui; Xu, Xiuli; Capon, Robert J.
Abstract: Chemical investigation on a Streptomyces sp. strain MS180069 isolated from a sediment sample collected from the South China Sea, yielded the new benzo[ f ]isoindole‐dione alkaloid, bhimamycin J (1 ). The structure was determined by extensive spectroscopic analysis, including HRMS, 1D, 2D NMR, and X‐ray diffraction techniques. A molecular docking study revealed 1 as a new molecular motif that binds with human angiotensin converting enzyme2 (ACE2), recently described as the cell surface receptor responsible for uptake of 2019‐CoV‐2. Using enzyme assays we confirm that 1 inhibits human ACE2 79.7 % at 25 μg/mL. Abstract :